2015
DOI: 10.1007/s11096-015-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Is a high maintenance dose of clopidogrel suitable for overcoming clopidogrel resistance in patients?

Abstract: A double maintenance dose of clopidogrel at 150 mg daily was associated with a reduction in adenosine diphosphate-induced platelet aggregation in South Korean patients who previously exhibited clopidogrel resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The present study showed that, in addition to its antiplatelet effects, clopidogrel showed anti-inflammatory activity; this was evidenced by the decreased serum levels of TNFα, ICAM-1, and RANTES, and heart tissue expression of TNFα, ICAM-1, IL-1β, and RANTES proteins. These findings were consistent with previous studies [22][23][24][25] and indicated that the cardioprotective effects of clopidogrel observed in the present study may be, in part, attributed to these anti-inflammatory effects.…”
Section: Wwwchinapharcom Zhang Y Et Alsupporting
confidence: 94%
“…The present study showed that, in addition to its antiplatelet effects, clopidogrel showed anti-inflammatory activity; this was evidenced by the decreased serum levels of TNFα, ICAM-1, and RANTES, and heart tissue expression of TNFα, ICAM-1, IL-1β, and RANTES proteins. These findings were consistent with previous studies [22][23][24][25] and indicated that the cardioprotective effects of clopidogrel observed in the present study may be, in part, attributed to these anti-inflammatory effects.…”
Section: Wwwchinapharcom Zhang Y Et Alsupporting
confidence: 94%
“…Increasing the dose can increase the biological effect of clopidogrel and reduce the incidence of CR. Simultaneously, large doses of clopidogrel can reduce patients' platelet aggregation rate with CR [126]. For PCI patients, the 600 mg loading dose has a faster response than the 300 mg loading dose and has a more substantial platelet inhibitory effect.…”
Section: Increase the Dose Of Clopidogrelmentioning
confidence: 99%